The Relationship Between Bullying Experience and Self-Concept among Adolescents - Retno Yuli Hastuti; Devi Permatasari; Sita Novia Rahmawati (Indonesian Journal of Global Health Research, 2021)
Bullying is a situation where an abuse of power is committed by a person or group of people. Bullying behavior experienced by adolescents can result in teenage self-concept being disrupted so that it can result in self-withdrawn or inferior. The results of the study showed that 58.4% of adolescents had high bullying experiences and 41.6% of adolescents had moderate bullying experiences at Junior High School in 2019. The purpose of this study was to determine the relationship between bullying experiences and self-concept in adolescents at Junior High School. This research method used a non- experimental quantitative design with a descriptive-analytic design. The sampling technique used was purposive sampling with a total sample of 89 respondents. Data collection was carried out after the result of the screening from 5 classes matched the inclusion criteria. Data analysis was performed using Rank Spearmen correlation showed that the p-value was 0.000, which means that there was a relationship between bullying and self-concept in adolescents in Junior High School. This study concluded that there was a significant relationship between the experience of bullying and self-concept in adolescents of Junior High School.